The ability of abaxial and adaxial epidermis of sun and shade leaves to attenuate UV-A and UV-B radiation in relation to the UV absorbing capacity of the whole leaf methanolic extracts - Liakoura, Vally; Bornman, Janet F.; Karabourniotis, George (Physiologia plantarum, 2003)
The UV‐absorbing capacity (measured as A310 cm−2 and A365 cm−2 or AUVR cm−2) of the shade leaves of four representative evergreen sclerophylls of the Mediterranean region (Quercus coccifera, Q. ilex, Arbutus andrachne and A. unedo) was considerably lower than the corresponding one of sun leaves of the same species. However, fibre optic microprobe measurements showed that adaxial as well as abaxial epidermis of shade leaves of all examined plants, except abaxial epidermis of A. andrachne, were almost as effective as the corresponding ones of the sun leaves in screening out most of the incident UV‐B radiation. There is probably a threshold, under which the concentration of the UV‐B absorbing compounds in the protective tissues is not furthermore reduced, in spite of the low levels of the stress factor (UV‐B radiation) in the environment. On the other hand, the ability of both abaxial and adaxial epidermis to attenuate UV‐A radiation, except of adaxial leaf epidermis of Quercus species, depended on the UV absorbing capacity of the whole‐leaf extracts, with different correlation patterns between the two Quercus species and the two Arbutus species. This could be explained by the fact that shade leaves showed not only quantitative, but also qualitative differences (higher A310/A365 ratio) in the absorbance of their methanolic extracts compared to these of sun leaves. The results of the present study showed that we should not always correlate the depth of penetration of UV radiation into sun and shade leaves according to the corresponding UV absorbing capacity of the whole leaf methanolic extracts, without taking into account all the anatomical, developmental and biochemical (such as different composition and distribution of the UV‐absorbing compounds among the different protective tissues) peculiarities of the leaves of each species.